Abject Relations : Everyday Worlds of Anorexia - Warin, Megan (Book collections on Project MUSE., 2010)
Abject Relations presents an alternative approach to anorexia, long considered the epitome of a Western obsession with individualism, beauty, self-control, and autonomy. Through detailed ethnographic investigations, Megan Warin looks at the heart of what it means to live with anorexia on a daily basis. Participants describe difficulties with social relatedness, not being at home in their body, and feeling disgusting and worthless. For them, anorexia becomes a seductive and empowering practice that cleanses bodies of shame and guilt, becomes a friend and support, and allows.